Unidirectional light scattering with high efficiency at optical frequencies based on low-loss dielectric nanoantennas - Albella,Echave P; Shibanuma,T; Maier,S (Nanoscale, 2016)
Dielectric nanoparticles offer low optical losses and access to both electric and magnetic Mie resonances. This enables unidirectional scattering along the incident axis of light, owing to the interference between these two resonances. Here we theoretically and experimentally demonstrate that an asymmetric dimer of dielectric nanoparticles can provide unidirectional forward scattering with high efficiency. Theoretical analyses reveal that the dimer configuration can satisfy the first Kerker condition at the resonant peaks of electric and magnetic dipolar modes, therefore showing highly efficient directional forward scattering. The unidirectional forward scattering with high efficiency is confirmed in our experiments using a silicon nanodisk dimer on a transparent substrate. This study will boost the realization of practical applications using low-loss and efficient subwavelength all-dielectric nanoantennas.